Development of Collage Activity-Based Media To Improve the Creativity of Fourth-Grade Students in Visual Arts Learning - A.Adinda Safirah Fatimah (Sains Global Institut, Indonesia, 2026)
This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The study aimed to develop collage activity-based media to improve the creativity of fourth-grade students in visual arts learning at the elementary school level. The media were developed based on an analysis of students’ needs and the characteristics of visual arts instruction. The results of the study indicate that the developed media met the feasibility criteria based on validation by material experts and media experts. The use of collage media was able to create a more active, engaging, and student-centered learning environment. In addition, this media generated positive responses regarding students’ participation in art-making activities, thereby helping to enhance creativity, imagination, and the ability to express ideas throughout the learning process. Based on the findings, collage activity media are suitable for use as an alternative innovative learning medium to create creative and meaningful visual arts learning in elementary schools.